National comprehensive cancer network recommendations for drugs without US food and drug administration approval in metastatic breast cancer: A cross-sectional study. (December 2020) - Etan, Tal; Amir, Eitan; Tibau, Ariadna; Yerushalmi, Rinat; Moore, Assaf; Shepshelovich, Daniel; Goldvaser, Hadar
Highlights: More than half of NCCN recommendations for metastatic breast cancer were off-label. Endocrine therapy and non-HER2 targeted drugs were more likely to be FDA approved. Chemotherapies and HER2 targeted recommendations were mostly off-label. Category 1 recommendations were more likely to be FDA approved. FDA approved recommendations were based on significantly higher sample size. Abstract: Background: National Comprehensive Cancer Network (NCCN) guidelines can include recommendations for off-label use of anti-cancer drugs. Here, we evaluate NCCN recommendations not supported by US Food and Drug Administration (FDA) approval and explore associations with such recommendations. Methods: All NCCN recommendations for MBC and their supporting data were identified. Drug labels were reviewed to determine whether recommendations are FDA approved. Logistic regression was used to compare FDA approved and off-label recommendations for pre-specified categories, including drug type, tumor subtype, level of recommendation and line of therapy. Results: Of 124 recommendations identified, 68 (55%) were off-label. Chemotherapy and human epidermal growth factor receptor 2 (HER2) targeted drugs were associated with lower odds of FDA approval (OR = 0.28, p = 0.001 and OR = 0.29, 95% p = 0.005, respectively). Recommendations for endocrine therapy (OR = 3.44, p = 0.009) and non-HER2 targeted treatment (OR = 10.0, p < 0.001) were more commonly FDA approved indications. Compared to combination therapies, monotherapies were more likely to be FDA approved (OR = 3.45, p = 0.001) as were category 1 (OR = 7.63, p = 0.001) and preferred NCCN recommendations (OR = 4.07, p < 0.001). Compared to off-label recommendations, NCCN recommendations of approved drugs were based on significantly higher sample size (mean 477 vs. 342 patients, p = 0.02) and were non-significantly associated with availability of randomized data (OR = 2.0, 95% CI 0.89–4.49, p = 0.09). Conclusion: More than half of all NCCN recommendations for MBC are off-label, mostly involving chemotherapy containing regimes for HER2 negative disease and combinations which include HER2-targeted drugs. Improved transparency of NCCN guidelines may result from reporting of the strength of the evidence supporting recommendations for MBC.